Awareness Logic: an Epistemological Defence Correlations between Awareness Logic and Epistemology. - Fernández-Fernández, Claudia (Sciendo, 2019)
with this paper, we intend to clarify some of the central notions that are commonly used in contemporary developments of Epistemic Logic, which lack a proper theoretical foundation. We want to follow the steps of some prominent epistemologists and epistemic logicians, who advocate for a correlation between their respective fields of study. We will proceed with a first small step that will consist in adapting one contemporary version of Epistemic Internalism to the framework of Awareness Logic, such that the key concepts in this logic can be sustained by an epistemological view, which, in turn, can work as a theoretical foundation for Awareness Logic.
Keywords: Lógica epistémica; Epistemology; Epistemic Internalism; Epistemic Logic; Awareness Logic; Justification